2023
DOI: 10.34067/kid.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Plasma Refill Rate and Intradialytic Hypotension During Hemodialysis: Retrospective Cohort Study With Causal Methodology

Abstract: Background: Attaining the optimal balance between achieving adequate volume removal while preserving organ perfusion is a challenge for patients receiving maintenance hemodialysis. Current strategies to guide ultrafiltration are inadequate. Methods: We developed an approach to calculate plasma refill rate throughout hemodialysis using hematocrit and ultrafiltration data in a retrospective cohort of patients receiving maintenance hemodialysis at 17 dialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…[85][86][87] One randomized trial using it to guide ultrafiltration rate during intermittent HD in critically ill patients showed no difference in hemodynamics or intradialytic complications. 88 While newer studies suggest novel methods to use blood volume monitoring to inform decisions regarding ultrafiltration, [89][90][91][92] these are at a preliminary phase and have only been studied in outpatients. It therefore remains unclear whether this technique will prove useful in the critical care setting.…”
Section: Avoiding Hypoperfusion Due To Fluid Removal Using Krtmentioning
confidence: 99%
“…[85][86][87] One randomized trial using it to guide ultrafiltration rate during intermittent HD in critically ill patients showed no difference in hemodynamics or intradialytic complications. 88 While newer studies suggest novel methods to use blood volume monitoring to inform decisions regarding ultrafiltration, [89][90][91][92] these are at a preliminary phase and have only been studied in outpatients. It therefore remains unclear whether this technique will prove useful in the critical care setting.…”
Section: Avoiding Hypoperfusion Due To Fluid Removal Using Krtmentioning
confidence: 99%
“…Therefore, establishing a means to avoid these fatal incidents is essential to achieving a good life prognosis for intermittent HD patients. Regarding hemodynamic instability, Wang et al reported that the plasma refilling rate at the start of HD and during dialysis is associated with intradialytic hypotension [3]. In this study, we focused on the fluctuations in body fluid properties and investigated the influence of electrolyte dynamics on myocardial excitability during treatment.…”
Section: Introductionmentioning
confidence: 98%
“…Waste products, fluids, and electrolytes that accumulate in the body during non-treatment times are removed from the body at a rapid rate during treatment. It is well known that fluctuations in body fluid properties and circulatory or hemodynamic instability caused by intermittent treatment are associated with dialysis imbalance syndrome and cardiac dysfunction [1][2][3]. Repeated cardiac dysfunction increases patients' chances of cardiac-related death [2].…”
Section: Introductionmentioning
confidence: 99%